2006
DOI: 10.1111/j.1524-4725.2006.32166.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate According to Grafted Density of Korean One-Hair Follicular Units with a Hair Transplant Implanter: Experience with Four Patients

Abstract: We think that 30 one-hair follicular units grafted with a KNU implanter is the proper density for better survival in Korean hair transplantation, and repeated sessions will be necessary for a better final result. However, we need further evaluation with a larger number of participants to overcome the small sample size and limitation of one-hair follicular unit grafts. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…One study of four patients determined that 20 to 30 onehair follicular units per cm 2 showed improved survival compared to grafts containing 40 to 50 equivalent follicular units. 43 The effect of preservation solution on graft viability has also been studied. 44 Prudent harvesting has consequential implications in graft survival, as transection of the follicular unit may lead to poor wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…One study of four patients determined that 20 to 30 onehair follicular units per cm 2 showed improved survival compared to grafts containing 40 to 50 equivalent follicular units. 43 The effect of preservation solution on graft viability has also been studied. 44 Prudent harvesting has consequential implications in graft survival, as transection of the follicular unit may lead to poor wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition there are several factors to determine fate of transplanted hair, such as the skill of the doctors, the amount of dissected perifollicular connective tissue, the time interval between harvesting and grafting, density of the transplanted hair, and the quality of the donor hair and scalp. 6,7 Donor dominance has been emphasized in autologous hair transplantation, while the influence of the recipient site was rather ignored. However, we previously reported that the hair growth pattern changes after eyebrow transplantation in patients with madarosis due to leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…The recipient area density suggested for the implanter is 30 grafts/cm 2 . 2,44,45 Because the donor supply is limited in Asians compared with Caucasians, a "density gradient" is advisable. If the patient wants to use a parting, then more density on the frontal area and part side is necessary.…”
Section: Recipient Sitementioning
confidence: 99%
“…• A density of 30 to 40 FUs/cm 2 or less is appropriate for Asians and permits the best hair survival rate. 42,43,44,45 Density Gradient and Layering Effect…”
Section: Optimal Density For Best Survival Ratementioning
confidence: 99%